KETERAMPILAN BERPIKIR KRITIS DAN AKTIVITAS MAHASISWA GENETIKA DAN EVOLUSI MELALUI PENERAPAN PBL DI PENDIDIKAN BIOLOGI UNIVERSIRTAS RIAU - Darmawati, Darmawati; Nursal, Nursal; Arnentis, Arnentis (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2021)
Background: Lecturers conducted genetics and evolution learning through the application of the PBL model so that students could develop critical thinking skills and activities , students can be more active and learning will be more meaningful. The purpose of this study is to determine the level of critical thinking skills mastery and student activity in genetics and evolution subjects which located on biology education at the University of Riau. Methods : The research was conducted at the Riau University Biology Education Study Program from September 2019 to January 2020. This type of research is quantitative descriptive research. The sampling technique is purposive sampling. Data collection techniques for critical thinking skills using LKM and for student activity data using observation sheets. The data analysis technique was done descriptively Results: The results showed that the average critical thinking skills for analyzing indicators : 76.245% (good), synthesizing : 74.92% (good), solving problems: 75.16% (good), and concluding : 82.77% (very good). The average for questioning activities : 63.98% (enough), responding : 70.96% (good), conducting discussions : 77.95% (good), conducting investigations : 82.69% (very good) and doing LKM : 82.47% (very good). Conclusion: Thus the average critical thinking skills of students is 77.27% (good) and the average student activity is 75.61% (good) in the genetics and evolution course through the application of PBL.